Implementasi Voice Recognition dan Sensor Ultrasonik pada Televisi - Ivani Resti Eisa; Derisma (Universitas Andalas, 2021)
Voice or speaker recognition is the ability of a machine or program to receive and interpret dictation or to understand and carry out spoken commands. Library is used by Voice recognition in this system is keras and tensorflow. Keras is one library often use for machine learning. Watching TV is a daily routine that is carried out by almost everyone from all walks of life.Most of them don't pay attention to the process and distance in watching TV.Sensor ultrasonic is used for detect object from TV in ideal distance.